Pengaruh insektisida deltametrin terhadap perilaku orientasi parasitoid Anagrus nilaparvatae (Pang et Wang) (Hymenoptera: Mymaridae) - Araz Meilin; Y. Andi Trisyono; Edhi Martono; Damayanti Buchori (Jurnal Entomologi Indonesia, 2015)
Host searching behaviour by a parasitoid includes orientation to the volatile compounds (odor) relesead by host or host plant. The aim of this study was to determine the changes in the orientation behaviour of Anagrus nilaparvatae (Pang et Wang), the egg parasitoid of rice brown planthoppers (Nilaparvata lugens (Stål)), after being exposed to sublethal concentrations of deltamethrin. The impact of residue on plants to the behaviour of parasitoid was also studied. The sublethal concentrations (LC10 and LC40) used were 0.023 ppm and 2.235 ppm, respectively. Deltamethrin applied to the rice plants were 12.5 ppm and 6.25 ppm, and its effect was observed at 3 hours, 1, 3 and 7 days after application. Orientation behavior was studied using Y-tube olfactometer. Application of deltamethrin at subletal concentration reduced the ability of surviving A. nilaparvatae to detect odors (volatile ompounds) released by the host, N. lugens. The higher the concentration of deltamethrin applied to the parasitoid or to the rice plants, the more prominent effect observed in the changing in the parasitoid behavious, in particular disruption to the parasitoid’s orientation to find their host. As consequences, effects of deltamethrin may lead to reduce the effectiveness of A. nilaparvatae as biological control agents in the field as a result of declining their searching capacity.